Raziskava ponudnikov poslovnih informacijskih rešitev za digitalno transformacijo podjetij - Bobek, Samo; Deželak, Zdenko; Šišovska Klančnik, Irena; Zabukovšek, Uroš; Sternad Zabukovšek, Simona (2023)
Research of Business Information Solution Vendors for Company Digital Transformation. The scientific monograph "A Study of Business Information Solutions Providers for Digital Transformation of Companies" addresses sustainable digital transformation, which is influenced by both the choice of technological platforms and the information architecture of digitized organizations. The European Union (EU) has identified digital transformation as one of the key areas of development. The European Commission has formulated and published a vision and guidelines for digital transformation, including EU goals in the field of digital transformation. The EU is also aware of the challenges related to pollution and climate change caused by pollution and their connection to digital transformation. The EU has published the "European Green Deal," which is based on the concepts of sustainable development of the United Nations (European Commission, 2021b). A comprehensive sustainability-oriented approach to digital transformation thus involves integrating business processes and digital technologies into digitized business operations. Therefore, the first part of the scientific monograph focuses on digital transformation and addresses how information technologies and solutions can impact the sustainable development of companies and society.In the second part of the scientific monograph, the modern concept of information architecture of digitized organizations is defined. Business information solutions play an important role in the digital transformation of organizations, as organizations use them for information support of their business processes and workflows. The most important representative of business information solutions is the comprehensive information solution (ERP solution). In addition, solutions for customer relationship management (CRM solutions), document management system solutions (DMS solutions), digital marketing solutions, and many others are classified as business information solutions. The second part of the scientific monograph describes the definitions and characteristics of these business information solutions and the providers of these solutions. It provides a detailed description of individual business information solutions available in the Slovenian market. Thus, the reader can gain an initial impression of the usefulness of individual solutions for a particular company or organization for each group of researched information solutions.
Keywords: digital transformation; sustainable development; technological platform; cloud computing; information architecture; comprehensive information solution (ERP); customer relationship management solutions (CRM); document management solutions (DMS); digital marketing solutions